Light controls edge functional groups to enhance membrane permeability - Sun, Tingyu; Wang, Lei; Hu, Rengkai; Li, Yangmei; Zhu, Zhi (Frontiers in Physics, 2023)
Functionalized membranes have high potential value in a broad range of practical applications and the functional groups at the membrane edge play a vital role in the permeability of the membranes. Here, based on an edge-functionalized graphene oxide (GO) membrane model, we theoretically report that high-frequency terahertz stimulation at the frequency near 44.0 THz can significantly enhance the water permeability of the membrane by nearly 5 times. Its mechanism was revealed to be that the stimulation amplified the C-O stretching of the functional groups and suppressed other vibration modes of the groups. As a result, the modulation of edge functional groups brings down the energy barricade of the membrane and allows water molecules to penetrate the GO membrane more easily. These findings provide a new perspective for enhancing membrane permeability by modulating particular functional groups such as the carboxyl on the edge of GO membrane.